2012
DOI: 10.1039/c2sm07342k
|View full text |Cite
|
Sign up to set email alerts
|

A computer simulation study of the anchoring transitions driven by rod–coil amphiphiles at aqueous–liquid crystal interfaces

Abstract: Dissipative particle dynamics simulations have been conducted to study the anchoring transitions of nematic liquid crystals in the presence of a rod-coil amphiphilic monolayer at the aqueous-liquid crystal interface. Instead of amphiphile interfacial coverage, the repulsion interaction parameter (a MR ) between the mesogens and rod blocks of the amphiphiles is used as a tunable and quantitative parameter to control the anchoring transition. Depending on a complicated interplay between the interfacial interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 31 publications
2
28
0
Order By: Relevance
“…The principle qualitatively drawn from these experiments is that, with increasing the amphiphile coverage, the amphiphile monolayer is packed more densely and orderly with the amphiphile tails stretching further, which allows the deeper penetration of LC molecules into the amphiphile monolayer and in turn induces homeotropic anchoring. Our simulation study 13 has further revealed that the tails of amphiphiles may act as an interfacial orientation eld in dictating the orientational ordering of LCs, which is in the same spirit as the conclusions of Bahr. 14,15 Moreover, recent work also suggests that the ordering of LCs also has a signicant effect on the interfacial assembly of amphiphiles.…”
Section: Introductionsupporting
confidence: 73%
See 3 more Smart Citations
“…The principle qualitatively drawn from these experiments is that, with increasing the amphiphile coverage, the amphiphile monolayer is packed more densely and orderly with the amphiphile tails stretching further, which allows the deeper penetration of LC molecules into the amphiphile monolayer and in turn induces homeotropic anchoring. Our simulation study 13 has further revealed that the tails of amphiphiles may act as an interfacial orientation eld in dictating the orientational ordering of LCs, which is in the same spirit as the conclusions of Bahr. 14,15 Moreover, recent work also suggests that the ordering of LCs also has a signicant effect on the interfacial assembly of amphiphiles.…”
Section: Introductionsupporting
confidence: 73%
“…For more details about the choice of bead number for each individual molecule we also refer to ref. 13. Note that three types of beads (M, R and C) are considered in our simulation systems.…”
Section: Simulation Methods and Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…LCs' aggregates such as spherical droplets, [13][14][15][16][17][18][19][20] flat surfaces 9,12,[21][22][23][24][25] or cylindrical formations (capillaries and bridges) [26][27][28][29][30] have been investigated. Kim et al quantified the optical, structural and topological features of tetrapodes assembled in flat layers, round capillaries and spherical droplets; the results for round capillaries revealed different textures depending on the inner diameter and system temperature.…”
Section: Introductionmentioning
confidence: 99%